A high throughput method for Monitoring of Sorafenib, regorafenib, cabozantinib and their metabolites with UPLC-MS/MS in rat plasma - Gu, Er-Min; Liu, Ya-Nan; Pan, Lvjun; Hu, Yingying; Ye, Xuemei; Luo, Pingping (Frontiers in Pharmacology, 2022)
As multi-targeted tyrosine kinase inhibitors, sorafenib, regorafenib and cabozantinib are widely used in hepatocellular carcinoma (HCC) for systemic therapies with anti-proliferative and anti-angiogenic effects. Nevertheless, adverse effects or insufficient efficacy appear frequently due to the plasma concentration with individual variability of these drugs. To ensure the curative effect and safety by therapeutic drug monitoring (TDM), this study developed a high throughput method to quantify sorafenib, regorafenib, cabozantinib and their active metabolites in plasma simultaneously. The chromatographic separation analysis achievement was performed on a Waters-ACQUITY UPLC BEH C18 column by UPLC-MS/MS system using a gradient elution of solvent A (acetonitrile) and solvent B (water with 0.1% formic acid) in 3.0 mins. This method presented satisfactory results of specificity, precision (the intra-day coefficient of variation was between 2.5–6.6%, and the inter-day coefficient of variation was between 4.0–11.1%) and accuracy (within ±15% for intra-day and inter-day), as well as the stability under certain conditions, the matrix effect in plasma, and extraction recovery (75.6–94.4%). The linearity of each analyte in the proper concentration scope indicated excellent. This study strictly complied with the performance rules of assay validation in biological medium proposed by FDA and was successfully applied to the pharmacokinetic study in rats. Thus, it would be an advantageous option to research the relationship between concentration-efficacy and concentration-toxic in HCC patients who were supposed to take these medications.